2003
DOI: 10.1007/s00418-003-0515-6
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein-1 and metallothionein-2 gene expression and localisation of apoptotic cells in Zn-treated LEC rat liver

Abstract: The aims of the present work were to determine the effect of long-term treatment with zinc (Zn) on metallothionein (MT) concentrations and to study the levels of both MT-1 and MT-2 mRNAs in Long-Evans Cinnamon (LEC) rat liver. We also identified apoptotic cells comparing two cytochemical techniques. Thirteen rats received 50 mg zinc acetate daily by gavage, 13 rats received no treatment, and both groups were killed after 60 days. Finally four rats were killed 35 days after birth (T 0 ). The results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Zn protected the Cu‐accumulating hepatocytes in the Zn‐treated animals, and therefore Cu‐caused adduct formation was there to be measured. In our previous study (26), we found an increased level of apoptosis in untreated rats compared with the treated one, leading to the conclusion that Zn supplementation prevents apoptosis. One antiapoptotic mechanism of Zn is its capacity to minimize oxidative damage to cellular organelles, thereby suppressing major signalling pathways leading to caspase activation and apoptosis: in this condition, reduced levels of DNA adducts are expected.…”
Section: Discussionmentioning
confidence: 67%
“…Zn protected the Cu‐accumulating hepatocytes in the Zn‐treated animals, and therefore Cu‐caused adduct formation was there to be measured. In our previous study (26), we found an increased level of apoptosis in untreated rats compared with the treated one, leading to the conclusion that Zn supplementation prevents apoptosis. One antiapoptotic mechanism of Zn is its capacity to minimize oxidative damage to cellular organelles, thereby suppressing major signalling pathways leading to caspase activation and apoptosis: in this condition, reduced levels of DNA adducts are expected.…”
Section: Discussionmentioning
confidence: 67%
“…Subsequently, cells were incubated with 0.3% H 2 O 2 ‐99% methanol for 15 min at room temperature and then with the primary mouse anti‐MT monoclonal antibody for 1 h at 37°C. This antibody has been characterized by Jasani and Elmes (25) and was applied at 1:10 dilution (26). Immunoreactions were revealed after incubation for 30 min at 37°C with biotinylated goat antimouse IgG secondary antibody, for 15 min with peroxidase‐conjugated streptavidin and for 3 min with DAB substrate–chromogen solution, using the Histostain™ Plus Kit (Zymed Laboratories, San Francisco, CA).…”
Section: Methodsmentioning
confidence: 99%
“…, ; Santon et al . ). It acts via up‐regulation of metallothionein in the liver and intestines, resulting in reduced copper absorption in the gut because of increased binding of copper to metallothionein in the intestinal cells lining the gut walls (Santon et al .…”
Section: Rodent Modelsmentioning
confidence: 97%
“…Zinc reduces hepatic, renal and intestinal copper and iron (Medici et al , 2005Santon et al 2003). It acts via upregulation of metallothionein in the liver and intestines, resulting in reduced copper absorption in the gut because of increased binding of copper to metallothionein in the intestinal cells lining the gut walls (Santon et al , 2003. Eight weeks of oral zinc acetate (50 mg/mL/day) initiated before the onset of hepatitis at 5 weeks of age prevents the onset of acute hepatitis (Medici et al 2005).…”
Section: Treatment Studiesmentioning
confidence: 99%